(3GdefUhQi aj GdWHs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf RcQjG GdQGRi (B: (3Efi LGeY ddCejQ CWGd Gddg HbGAg ai cJGHi gPG ,fcJkG hYjhfkG ef UfGYI GdWH , eJMQHkG ai Pdc GdGNJUGQ hGdEjLGR , hPGcQkG ai MaX GdUMI heYGdLI GdCeQGV s
(3BNQgG (B:s
(3hEPG bO HjfG Ydi LejY GdebGdGJ hGdaUhd GdePchQI ai UOQ gPG GdcJGH ajced cJGHfG gPG ai GdehVY hHGddg GdJhajb hYdjg GdEYJeGO s
(3fSNI NGeSIs
(3hHBNQgG ebGHdI eDQNI HSfI (B1147(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B256 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH JjehQ (B129) s
Keywords: (3GdWHs